Risk of rod fracture according to cross-link position in pedicle subtraction osteotomy (PSO): A finite element study. (March 2020) - Hong, Je Beom; Son, Dong Min; Park, Tae Hyun; Woo, Su Heon; Lee, Sung Jae; Choi, Un Yong; Han, In-bo; Chung, Chun Kee; Kim, Yongjung Jay; Sohn, Seil
Highlights: We aim to investigate the effects of cross-link position on rod stress in lumbar pedicle subtraction osteotomy (PSO) site by using finite element model (FEM). The geometry and dimensions of FEM were obtained from a high-resolution computed tomography scan data of a 65 years old female patient with spinal sagittal imbalance. The peak von mises stress (PVMS) of rod at PSO site decreased as the cross-link is located apart from the PSO site during flexion and extension. Cross-link at two levels apart from the PSO site does not increase the risk of rod fracture. Abstract: Purpose: The purpose of this study is to investigate the effect of the cross-link position on the rod fracture phenomenon during pedicle subtraction osteotomy (PSO) surgery using finite element model (FEM). Methods: A three-dimensional finite element model of a lumbar spine with sagittal imbalance was constructed using computed tomography data of a 65-year-old female patient. After simulating the standard PSO at the L4 level, we constructed four models, specifically a model without a cross-link and three models with a cross-link at three different sites. The peak von Mises stress (PVMS) of the rod around the PSO site was measured after applying physiological loads (flexion, extension, axial rotation, and lateral bending) in each model. Results: The measured PVMS outcomes at the PSO site were 135.8, 135.9, 208.9, and 384.7 MPa for model 1, 2, 3, and 4 during flexion, and 180.0, 180.1, 210.1, and 445.7 MPa during extension. These results show that when the cross-link is located at the PSO site, the rod stress at the PSO site increases significantly during flexion and extension. As the cross-link moved away from the PSO site, the effect on the rod stress decreased. When the cross-link was placed two levels away from the PSO site, the rod stress was scarcely affected. Conclusion: When the cross-link during PSO surgery was positioned two levels away from the PSO site, the risk of rod fracture did not increase.